Relationship between parental attachment, parental differential treatment, sibling relationship, peer attachment and positive well-being among adolescents in the Klang Valley, Malaysia - Rajendran, Kogilavani (2018)
The positive development view emphasizes the possibility of adolescents to follow a positive development based on strengths, positive qualities and favorable environments. Therefore identifying the protective factors that could affect positive well-being of adolescents is essential. The aim of the study is to examine the relationship between parental attachment, parental differential treatment, sibling relationship and peer attachment with positive adolescent well-being. The study also aims to examine the role of gender as moderator for links between parental attachment, parental differential treatment, sibling relationship and peer attachment with positive adolescent well-being. The study involves participation of 400 Form 1 students from government schools in the state of Kuala Lumpur and Selangor. Four instruments which are Positive Youth Development Scale, Inventory of Parent and Peer Attachment, Sibling Relationship Questionnaire and Inventory of Differential Experience were used in this study. The descriptive analysis showed that adolescents positive well-being was affected by parent’s age, mother’s years of education and family monthly income. Gender difference was found among girls and boys on positive well-being where girls had higher positive well-being compared to boys. The result also showed that there are six predictor variables contributing to adolescent positive well-being. The study also found that gender moderated the relationship between paternal attachment, maternal differential affection, paternal differential affection, paternal differential control, sibling relationship and peer attachment with adolescent positive well-being. This study shows the protective factors that could contribute to higher positive well-being among adolescents. The findings of the study is in line with the theories formed the theoretical framework of this study, whereby family and peer are important factors in shaping adolescents’ positive well-being. This study had provided information on factors that can help adolescent’s positive development. Identifying these factors will provide insight on what events or experiences will reduce the likelihood of negative outcomes and increase the likelihood of positive outcomes. These information of contributing factors on adolescent positive well-being would provide opportunities to develop programs to help enhance positive development of adolescents in Malaysia.